2023
DOI: 10.1002/nbm.5030
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of alterations in interstitial fluid dynamics in cases of whole‐brain radiation using the diffusion‐weighted image analysis along the perivascular space method

Toshiaki Taoka,
Rintaro Ito,
Rei Nakamichi
et al.

Abstract: In the current study, we assessed changes in interstitial fluid dynamics resulting after whole‐brain radiotherapy using the diffusion‐weighted image analysis along the perivascular space (DWI‐ALPS) method, which is a simplified variation of the diffusion tensor image ALPS (DTI‐ALPS) method using diffusion‐weighted imaging (DWI) with orthogonal motion‐probing gradients (MPGs). This retrospective study included 47 image sets from 22 patients who underwent whole‐brain radiotherapy for brain tumors. The data for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
2
2
0
Order By: Relevance
“…Compared with patients in the pre-RT group, those in the post-RT group had a significantly lower DTI-ALPS index. This finding is consistent with that of a recent diffusion-weighted imaging study in which the diffusion-weighted imaging-ALPS index was significantly lower in the post-radiation group than in the control group (Taoka et al, 2023). A decreased DTI-ALPS index may thus indicate glymphatic system insufficiency in patients with NPC following RT.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Compared with patients in the pre-RT group, those in the post-RT group had a significantly lower DTI-ALPS index. This finding is consistent with that of a recent diffusion-weighted imaging study in which the diffusion-weighted imaging-ALPS index was significantly lower in the post-radiation group than in the control group (Taoka et al, 2023). A decreased DTI-ALPS index may thus indicate glymphatic system insufficiency in patients with NPC following RT.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings of significant negative correlations between the MDRT and the DTI-ALPS index indicate that a higher ipsilateral maximum RT dosage is associated with a lower DTI-ALPS index. This expected finding implies that glymphatic functional impairments are mainly induced by RT, and is in line with one recent whole-brain radiation study showing that the ALPS index has a weak negative correlation with biologically equivalent RT doses (Taoka et al, 2023). Moreover, using rat models, several studies have reported that increased single or total radiation doses result in elevated inflammatory factors (such as tumor necrosis factor-α, interferon-γ, and interleukin-1β), cellular debris, and BBB permeability, and have a negative effect on perivascular astrocyte survival (Chiang et al, 1993;Raju et al, 2000;Yuan et al, 2003;Yang et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…There was a weak negative correlation between ALPS and irradiation dose. 91 When performing the DWI-ALPS method, it is important to note that, unlike the DTI method, the positional relationship between white matter fibers and the ROI cannot be adjusted in post-processing, so the transverse section must be perpendicular to the projection fiber at the time of imaging.…”
Section: Variation Of Alps Methodsmentioning
confidence: 99%
“…A number of studies using the DTI-ALPS method have evaluated the association between age and ALPSindex. 4,17,18,[27][28][29]36,43,56,61,70,74,78,[80][81][82][83][84][85][86][87][88][89][90][91][92] Among these reports, a number of them showed negative correlations between age and ALPS-index. McKnight et al showed a negative correlation between the ALPS-index and age in a group of subjects with PD or essential tremor aged approximately 40−80 years, with a correlated Spearman's rank correlation coefficient of −0.203.…”
Section: Findings On the Agingmentioning
confidence: 99%